Influenza vaccination campaigns targeted at healthcare workers:results of four hospitals in Rome. (13th November 2019) - Tognetto, A; Abbondanzieri, A; Cerone, G; Di Pumpo, M; Nardi, A; Paglione, L; Franco, E; La Torre, G; Orsi, G B; Laurenti, P
Abstract: Background: Seasonal influenza vaccination (SIV) of health care workers (HCWs) is well recognized as a public health measure that can protect both HCWs from infection and patients from the risk of influenza complications. Nevertheless, vaccination coverage rates among this specific population result generally lower than the recommended target. With our study, we aimed to describe the activities and the outcomes of four different SIV campaigns targeted at HCWs and organized during the season 2018/2019 in four hospitals in Rome. Methods: A cross-sectional study involving four teaching hospitals was performed. The collected data were synthetized into a set of descriptors and indicators, validated through a previous study that had involved the same Centers. Results: The Medical Directorates, in collaboration with the University Hygiene and Public Health Units of the four hospitals organized different strategies: Hospital 1, 3 and 4 realized educational courses for HCWs and actively promoted the campaigns through e-mail invitations to all HCWs. As for the access to vaccination, all the hospitals provided a dedicated unit for SIV; Hospital 1 and Hospital 4 organized also on-site vaccination sessions in the hospital wards, that required a large number of staff. The vaccination coverage rates resulted: 22.37% in Hospital 1, 18.10% in Hospital 4, 9.28% in Hospital 2 and 8, 51% in Hospital 3. Conclusions: Our results demonstrate that multi-activity campaigns, involving education, promotion and easy access to vaccination constitute an effective approach to reinforce the value of SIV. Our findings suggest that on-site vaccination may play a key role in determining a higher vaccination coverage. Key messages: Multi-activity vaccination campaigns, involving education, promotion and easy access to vaccination constitute an effective approach to reinforce the value of seasonal influenza vaccination for HCWs. On-site vaccination may play a key role in determining a higher vaccination coverage.